Could zinc prevent reproductive alterations caused by cigarette smoke in male rats? - Garcia, Patricia Carvalho [UNESP]; Piffer, Renata Carolina [UNESP]; Cecatto Gerardin, Daniela Cristina; Sankako, Michele Kimie [UNESP]; Alves de Lima, Rodrigo Otavio; Marques Pereira, Oduvaldo Camara [UNESP] (CSIRO Publishing, 2012)
The aim of the present study was to evaluate the effects of zinc on fertility through semen parameters, testosterone level and oxidative DNA damage to spermatozoa of rats exposed to cigarette smoke. Male Wistar rats (60 days old) were divided into four groups (n = 10 per group): control, cigarette-smoking (20 cigarettes per day), zinc (zinc chloride 20 mg kg(-1) day(-1)) and zinc plus cigarette-smoking (zinc chloride 20 mg kg(-1) day(-1); 20 cigarettes per day). The treatment was applied for nine weeks and the following parameters were analysed: bodyweight, wet weights of the reproductive organs and the adrenal gland, plasma testosterone concentration, testicular function (seminal analysis and daily sperm production) and sperm DNA oxidative damage. The exposure to cigarette smoke decreased testosterone concentration, the percentage of normal morphology and the motility of spermatozoa. In addition, this exposure increased sperm DNA oxidative damage. Zinc treatment protected against the toxic damage that smoking caused to spermatozoa. This study showed a correlation between smoking and possible male infertility and subfertility, and also that the majority of smoking-induced changes in spermatozoa were prevented by zinc treatment. In conclusion, zinc, an antioxidant and stimulant of cell division, can be indicated as a promising treatment in men with infertility caused by the toxic components of cigarette smoke.
Keywords: semen parameters; spermatozoa; testicular function